2006
DOI: 10.1186/1748-717x-1-18
|View full text |Cite
|
Sign up to set email alerts
|

3D-conformal-intensity modulated radiotherapy with compensators for head and neck cancer: clinical results of normal tissue sparing

Abstract: Background: To investigate the potential of parotic gland sparing of intensity modulated radiotherapy (3D-c-IMRT) performed with metallic compensators for head and neck cancer in a clinical series by analysis of dose distributions and clinical measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The motivation behind improved beam angle selection stems from the continued need to decrease the dose to critical organs. This need is validated by clinical studies that show decreased toxicity is associated with lower critical organ doses (Marmiroli et al 2005, Wendt et al 2006, Arcangeli et al 2007, Kuban et al 2008. While we have not explicitly addressed the issue in this paper, as tumor dose-response relationships continue to be validated through clinical trials, the need for addressing critical organ toxicity assumes greater significance.…”
Section: Discussionmentioning
confidence: 93%
“…The motivation behind improved beam angle selection stems from the continued need to decrease the dose to critical organs. This need is validated by clinical studies that show decreased toxicity is associated with lower critical organ doses (Marmiroli et al 2005, Wendt et al 2006, Arcangeli et al 2007, Kuban et al 2008. While we have not explicitly addressed the issue in this paper, as tumor dose-response relationships continue to be validated through clinical trials, the need for addressing critical organ toxicity assumes greater significance.…”
Section: Discussionmentioning
confidence: 93%
“…Preventive strategies of salivary gland hypofunction and dry mouth secondary to RT have focused on the preservation of salivary gland function, primarily the parotid glands, by new advances in radiation techniques, including the appearance and optimizing of 3D treatment planning, conformal radiation techniques, and intensity-modified radiotherapy (IMRT) [ 20 , 21 ]. Recent studies also showed that the prevention of hyposalivation secondary to RT may be addressed via use of cytoprotective agents (eg.…”
Section: Sgd Secondary To Cancer Treatmentmentioning
confidence: 99%